#### Answer

(r+6)(r-7)

#### Work Step by Step

$r^{2}$ -r -42=$r^{2}$ -7r +6r-42=
r(r-7)+6(r-7)=(r+6)(r-7)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

(r+6)(r-7)

$r^{2}$ -r -42=$r^{2}$ -7r +6r-42=
r(r-7)+6(r-7)=(r+6)(r-7)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.